2005
DOI: 10.1002/cncr.21448
|View full text |Cite
|
Sign up to set email alerts
|

Precision radiotherapy for hemangiopericytomas of the central nervous system

Abstract: Objective Sleepiness at the wheel is a major risk factor for traffic accidents. Because of the potential medical and legal implications, in this study, we evaluated the correlation between subjective and objective measures of sleepiness and driving performances in patients suffering from excessive daytime sleepiness. Methods Thirty‐eight untreated sleep apnea patients (mean age ± standard deviation, 51 ± 9 years; mean apnea–hypopnea index ± standard deviation, 41 ± 25), and 14 healthy control subjects (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 132 publications
0
47
0
6
Order By: Relevance
“…The 5-, 10-, and 15-year recurrence rates for irradiated tumors were 38, 64, and 80 %, respectively. The effective radiation dose is quoted by most studies to be [50 Gy [17][18][19][21][22][23][24]. In a recent systematic review of 563 intracranial HPCs cases (277 had follow-up data), Rutkowski et al [25] reported that patients receiving [50 Gy of radiation had worse survival outcomes (median Table 2 Cases of hemangiopericytoma of the spine described in present and previous reports survival 4 vs. 18.6 years, p \ 0.01).…”
Section: Adjuvant Treatmentmentioning
confidence: 69%
“…The 5-, 10-, and 15-year recurrence rates for irradiated tumors were 38, 64, and 80 %, respectively. The effective radiation dose is quoted by most studies to be [50 Gy [17][18][19][21][22][23][24]. In a recent systematic review of 563 intracranial HPCs cases (277 had follow-up data), Rutkowski et al [25] reported that patients receiving [50 Gy of radiation had worse survival outcomes (median Table 2 Cases of hemangiopericytoma of the spine described in present and previous reports survival 4 vs. 18.6 years, p \ 0.01).…”
Section: Adjuvant Treatmentmentioning
confidence: 69%
“…Some investigators have recommended that postoperative radiotherapy should be implemented to control the residual tumor (11,13,14,19,52,55). In fact, adjuvant radiotherapy has been shown to be effective in controlling HPC (11,13,14,19,30,55). However, the evidence of its efficacy has been mainly based on small retrospective studies.…”
Section: A B Cmentioning
confidence: 99%
“…They were first described by Stout and Murray in 1942 (47). HPCs may occur anywhere in the human body but the most common locations are the extremities, pelvis, the retroperitoneum, and the head and neck areas (11). They are rarely found in the central nervous system and account for approximately 2% to 4% of all primary meningeal tumors (19,33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of HPC are in soft tissues and can be reclassified as a fibroblastic neoplasm similar to a solitary fibrous tumors (2)(3)(4). The most common sites of HPC are the lower extremities, followed by the pelvis and head and neck (5,6). HPC has non-specific image features and clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%